Single-ion magnetism in seven-coordinate YbIII complexes with distorted D5h coordination geometry. Issue 38 (18th September 2017) - Wu, Dong-Qing; Shao, Dong; Wei, Xiao-Qin; Shen, Fu-Xing; Shi, Le; Zhang, Yi-Quan; Wang, Xin-Yi
Abstract : Two seven-coordinate compounds of pentagonal bipyramidal Yb III centers exhibiting field-induced slow magnetic relaxation were characterized structurally and magnetically. Abstract : Two seven-coordinate compounds with pentagonal bipyramidal Yb III centers, namely, [Yb(H3 Bmshp)(DMF)2 Cl2 ]·DMF·1.5H2 O (1 ) and [Yb(H3 Bmshp)(DMF)2 Cl2 ]·H4 Bmshp (2 ) (H4 Bmshp = (2, 6-bis[(3-methoxysalicylidene)hydrazinecarbonyl]-pyridine)) were synthesized by changing the molar ratio of reactants in DMF. The structures of compounds1 and2 are very similar, except for the existence of different lattice molecules: one DMF and one and a half water molecules in1, and one neutral uncoordinated ligand in2 . The coordination geometries of both the pentagonal bipyramidal Yb III centers (YbCl2 N1 O4 ) in compounds1 and2 are also very similar with only slight differences. Magnetic data analyses revealed that the subtle structure variations result in remarkable different slow magnetic relaxation properties of compounds1 and2 . To further understand their magnetic behaviors, ab initio calculations were performed for both compounds1 and2 . The calculated results indicate that the magnetic anisotropies of compounds1 and2 are significantly different: easy-plane magnetic anisotropy for1 and easy-axis magnetic anisotropy for2 . To the best of our knowledge, these compounds are the first Yb III -based SIMs of pentagonal bipyramidal geometry.